Effect of sago frond stored at room temperature on free reducing sugars - Siti Zulaikha, Mobd Abdullah (Universiti Malaysia Sarawak, 2017)
A study was conducted to determine the effects of storage duration on reducing sugars from sago frond (SF) petiole. Fresh sago frond was sampled and kept at ambient temperature in the laboratory. The sago frond was divided into three different experiments which were determination of weight reduction, moisture content and reducing sugar concentration. Three replicates of experiment were conducted in each day for 10 days storage duration. It was investigated that effect of weight reductions was highest on day 10, where about 83.5 g weight loss compared to the other days. Besides that, the loss of moisture content was above 12 % on each day from day 0 until day 8. This indicates the absorption of moisture from surrounding of about more than reducing moisture during storage period. Other than that, the highest reducing sugars concentration was on day 6 that was about 58.96 g/L and 2.54 % was the highest sugar recovery, which is on day 10.